Espacialização das pressões do avanço do capitalismo nas áreas indígenas do estado de Rondônia - Brasil - Silva, Carlandio Alves da (2021)
The work presented here is the result of a study carried out on the spatialization of the pressures that involve the Indigenous Lands and the application of the Socioeconomic Ecological Zoning in the state of Rondônia. In this sense, the geographical scale was used to delimit the periodization of temporal space in the research and concepts of syntagmatic and paradigmatic actors to indicate the modifying agents of the ecological socioeconomic zoning and which impose pressures around the Indigenous Lands. In this perspective, it was found that since the arrival of Europeans, ethnic groups are constantly attacking the withdrawal of their dominion over their land, remembering that the legislation directed at indigenous areas does not place them as owners of the land, they need state authorizations, the latter as a syntagmatic actor par excellence, imposes his will on his land on indigenous peoples. The methodological procedures used to construct this dissertation had the perspective of analyzing Critical Geography, with materialism-historical-dialectical being the main source. The approach to the themes was centered on the notions of geographic scale. Using the geographic scale to delimit temporal space in the research, it was carried out to reflect in a macro and micro scale with the approach of the theme, where the analysis of zoning was done as an instrument of territorial ordering for the state of Rondônia, in which indigenous areas are inserted, in this perspective, it was necessary to carry out a periodization that encompasses both the issue of space. Therefore, we sought to relate the local space in which the indigenous people lived and resist today, to the phenomena of the macro space, to which the spatialization of capitalism is and are exposed, describing the processes that involved their social structures. It was first observed that POLONOROESTE had as a principle the connection of Rondônia through the opening and paving of BR 364 with the rest of the country and directed colonization, for the effectiveness of the plan, the protection factor for forests and indigenous areas was not observed, and this was one of the causes that the World Bank pressured Brazilian politicians to change the situation. In response, PLANAFLORO was planned, because unlike POLONOROESTE, it tried to balance economic growth with the preservation of nature, indicating that development could occur in conjunction with sustainability. In his objective c, he makes it very clear that the ZSEE should have as a priority to care for and maintain the limits of indigenous reserves, in this sense it must be made clear that it is not his competence to manage on indigenous land, but to protect it from its limits.